2019
DOI: 10.1007/s00204-019-02547-x
|View full text |Cite
|
Sign up to set email alerts
|

Critical assessment and integration of separate lines of evidence for risk assessment of chemical mixtures

Abstract: Humans are exposed to multiple chemicals on a daily basis instead of to just a single chemical, yet the majority of existing toxicity data comes from single-chemical exposure. Multiple factors must be considered such as the route, concentration, duration, and the timing of exposure when determining toxicity to the organism. The need for adequate model systems (in vivo, in vitro, in silico and mathematical) is paramount for better understanding of chemical mixture toxicity. Currently, shortcomings plague each m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(40 citation statements)
references
References 110 publications
0
40
0
Order By: Relevance
“…In real-life scenarios, the general population experiences uncontrolled multi-chemicals low-dose exposure from many different sources [1][2][3][4][5]. Epidemiological and biomonitoring studies have shown that exposure to chemical mixtures is associated with various adverse health effects as a consequence of different types of toxicity, such as neurotoxicity, cardiotoxicity, hematotoxicity, nephrotoxicity, hepatotoxicity, as well as endocrine disruption [2,[5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In real-life scenarios, the general population experiences uncontrolled multi-chemicals low-dose exposure from many different sources [1][2][3][4][5]. Epidemiological and biomonitoring studies have shown that exposure to chemical mixtures is associated with various adverse health effects as a consequence of different types of toxicity, such as neurotoxicity, cardiotoxicity, hematotoxicity, nephrotoxicity, hepatotoxicity, as well as endocrine disruption [2,[5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the already identified and well-established chemicals with endocrine-disrupting properties include organochlorine pesticides, polybrominated diphenyl ethers, polychlorinated biphenyls, toxic metals, as well as phthalates and bisphenol A [1,[20][21][22][23]. The results from a recent nation-wide survey of the levels of environmental contaminants among pregnant women in France showed that these chemicals are quantifiable in virtually all individuals [24].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of modern lifestyle, stress factors including malnutrition/overnutrition, smoking or sedentary routine are initiating factors for the impairment of inflammatory pathways contributing to the development of NCDs. Furthermore, in real-life scenarios, people experience uncontrolled simultaneous exposure to many environmental chemicals, hence novel methodological approaches simulating real-life exposures are being developed under the name real life risk simulation (RLRS) with the aim to assess the potential adverse health effects of long-term exposure to chemical mixtures (Hernandez et al, 2019;Hernandez and Tsatsakis, 2017;Tsatsakis et al, 2016Tsatsakis et al, , 2019a. According to WHO, 80% of NCDs-related deaths could be prevented by changes in these modifiable risk factors, and recent evidence identified unhealthy diet as the biggest risk factor for NCDs-related deaths (Collaborators, 2019;WHO, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of combining multiple registered medicines present on the market, in order to increase the effectiveness of the therapy, is yet another advantage of the approach (Pushpakom et al, 2018). However, these new combinations of medications certainly present a safety risk, since most of these medicines have the potential to cause numerous side effects when used in monotherapy and their combined used can produce new or more pronounced toxic effects as it is the case with chemicals (Hernandez et al, 2019;Karri et al, 2020;Kostoff et al, 2020;Tsatsakis et al, 2019). Moreover, the health status of patients with COVID-19 disease is often complicated by co-existing illnesses, so particular attention should be paid to the adverse/toxic effects of the drugs and their combinations used in potential therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%